The response of Malaysia and Turkey on covid-19 pandemic: A comparative analysis - Asmady Idris; Omer Kurtbag; Asri Salleh (Iranian Association of Geopolitics, 2021)
Malaysia and Turkey are progressive, modern Muslim-majority countries. Both have shown strong resolve and capabilities in dealing with issues and challenges both at home and international level. In dealing with COVID-19 pandemic, both countries have adopted various measures and strategies to contain the virus outbreak. Yet, the biggest challenge in executing those is balancing the need to protect the public and maintain economic growth. Hence, this study compares and contrasts the measures and strategies taken by both countries in containing the COVID-19 outbreak as well as ensuring the continuity of economic growth. The time period of this study was from March 2020 until early February 2021 as most of the countries, including Malaysia and Turkey, by then had introduced new COVID-19-related health policies and economic stimulus packages. The finding compares and contrasts the effectiveness of those measures and strategies so that both countries can share and learn from this pandemic.